2014
DOI: 10.1074/jbc.m114.569434
|View full text |Cite
|
Sign up to set email alerts
|

Gluconeogenesis in Leishmania mexicana

Abstract: Background: Essential gluconeogenesis pathway in Leishmania parasites is poorly understood. Results: Glycerol kinase, phosphoenolpyruvate carboxykinase, and pyruvate phosphate dikinase allow the entry of glycerol, aspartate, and alanine into Leishmania mannogen, respectively. Conclusion: Contribution of these enzymes into gluconeogenesis differs between promastigotes and amastigotes. Significance: This valuable information may help establish amastigote-specific metabolic models, which could reveal new therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…In C. thermocellum , PPDK was similarly found to be up regulated on α-cellulose at stationary phase compared to cellobiose [ 7 ]. PPDK plays an anabolic role in gluconeogenesis in some organisms [ 43 , 44 ], and functions in the catabolic direction in others [ 40 , 45 ]. As has been shown in Thermoproteus tenax [ 40 ], the simultaneous presence and expression of PPDK with PPK in C. termitidis may represent allosteric differential regulation, thereby providing a way in controlling the inter-conversion of phosphoenolpyruvate and pyruvate and allowing adaptation to different conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In C. thermocellum , PPDK was similarly found to be up regulated on α-cellulose at stationary phase compared to cellobiose [ 7 ]. PPDK plays an anabolic role in gluconeogenesis in some organisms [ 43 , 44 ], and functions in the catabolic direction in others [ 40 , 45 ]. As has been shown in Thermoproteus tenax [ 40 ], the simultaneous presence and expression of PPDK with PPK in C. termitidis may represent allosteric differential regulation, thereby providing a way in controlling the inter-conversion of phosphoenolpyruvate and pyruvate and allowing adaptation to different conditions.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study of carbon metabolism reported by Saunders and colleagues, revealed glucose to be the dominant carbon source with aspartate also entering the TCA cycle but other amino acids or fatty acids having little or no role [ 2 ]. Another study, however, indicated that utilisation of amino acids for mannogen biogenesis was highly dependent upon the presence or absence of glucose in the culture medium [ 39 ]. Following the distribution of carbons from labelled glucose here we confirmed that glucose is the main carbon source for the TCA cycle in WT parasites under standard culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…38 In these processes, glucose and other hexoses are critical cellular nutrients to Leishmania parasites, where these parasites (promastigote or amastigote life form) are able to import sugar from the extracellular environment or synthesize de novo, via gluconeogenesis. 39 Promastigote parasites made both process, but amastigote parasites only carry out gluconeogenesis process. 39 Glyceraldehyde 3-phosphate dehydrogenase Leishmania major (PDB ID: 1GYP and 1A7K, see Fig.…”
Section: Oxidoreductases (Ec 1)mentioning
confidence: 99%
“…39 Promastigote parasites made both process, but amastigote parasites only carry out gluconeogenesis process. 39 Glyceraldehyde 3-phosphate dehydrogenase Leishmania major (PDB ID: 1GYP and 1A7K, see Fig. 4) belongs to oxidoreductase group and participate in Pentose Phosphate and glycolysis metabolic pathways.…”
Section: Oxidoreductases (Ec 1)mentioning
confidence: 99%